Bio-inspired high-performance solid-state supercapacitors with the electrolyte, separator, binder and electrodes entirely from kelp. Issue 48 (27th November 2017) - Zeng, Juan; Wei, Lu; Guo, Xin
Abstract : Biocompatible and renewable solid-state supercapacitors with all the key components entirely from a single precursor kelp demonstrate outstanding electrochemical performance. Abstract : This is the first report on a type of solid-state supercapacitor with all the key components, including the electrolyte, separator, binder and electrodes, coming entirely from a single precursor: kelp, an abundant and economic food resource in the ocean. The alginate hydrogel electrolyte, alginate membrane separator and alginate binder developed for constructing supercapacitors are all from the extract of kelp, i.e. sodium alginate, which is an ionic conductive and high-modulus natural polysaccharide, and is food and skin safe. The activated carbon electrode material produced directly from kelp presents a 3D hierarchical porous architecture, having a high specific surface area of 4425 m 2 g −1 and a high pore volume up to 3.22 cm 3 g −1 . Such a novel cell construction provides the solid-state supercapacitor with high ionic conductivity and low interface resistances, and thus excellent electrochemical performance, including a high specific capacitance of the electrode (277 F g −1 or 88.2 F cm −3 ), fast rate capability (156 F g −1 retained at 20 A g −1 ) and good stability both in the cycling test and in the constant voltage hold test. The electrochemical performance of the "all- kelp " supercapacitor is the best among all carbon-based solid-state supercapacitors reported in the literature. Moreover, the "all- kelp " supercapacitor is environmentally friendly and biocompatible, particularly suitable for advanced implantable medical devices and wearable electronics, in which the safety and reliability are especially important.